Frequency And Amount Of Animal And Plant Protein Consumption In Relation To Hemoglobin Levels In Adolescent Girls - Safitri, Nur Aulia; Widyaningsih, Endang Nur (Jurnal Pangan Gizi dan Kesehatan, 2026)
Background: Anemia remains a major nutritional problem among adolescent girls and can adversely affect health, academic performance, and the quality of human resources. Protein intake, derived from both animal and plant sources, plays an important role in hemoglobin synthesis. Objectives: This study aimed to analyze the relationship between the frequency and amount of animal-based and plant-based protein consumption and hemoglobin levels among adolescent girls at SMAN 1 Kartasura. Method: This study employed an observational cross-sectional design. A total of 90 female students from grades X and XI were selected using simple random sampling. Protein intake data were collected through interviews using a Semi- Quantitative Food Frequency Questionnaire (SQ-FFQ), while hemoglobin levels were measured using the cyanmethemoglobin method. Data were analyzed using univariate and bivariate analyses with the Chi-square test. Results: The results showed that most respondents had normal hemoglobin levels (66.7%). Higher frequencies of animal and plant protein consumption tended to be associated with normal hemoglobin levels; however, no significant association was found between the amount of animal protein intake (p = 0.134) or plant protein intake (p = 0.266) and hemoglobin levels. Conclusion: This study concludes that protein consumption contributes to maintaining normal hemoglobin levels, although hemoglobin status in adolescent girls is influenced by multiple factors, including food quality, iron bioavailability, and overall dietary patterns.